Regionalist mobilization and new regional powers: the administrative fragmentation of Viejo Caldas and the creation of Risaralda - López Pacheco, Jairo Antonio (Sociedad y Economía, 2011)
This paper looks to an approach to the process of creation of Risaralda’s department in 1966 and to the establishment of a new regional power rooted in the formation and performance of a regionalist mobilization. The paper arises the movement’s efficiency as an instance of the existence of a diferenciated social space, in which a new elite with particular features of solidarity, identity and cohesion obtained to  dominate the power’s balances and to establish a political and social power legitimated by an identity discourse.